The Radial Anisotropy of the Continental Lithosphere From Analysis of Love and Rayleigh Wave Phase Velocities in Fennoscandia - Maupin, Valerie; Mauerberger, Alexandra; Tilmann, Frederik (Journal of Geophysical Research: Solid Earth, 2022)
Radial anisotropy (RA) in the upper mantle of the Fennoscandian Shield is analyzed by joint inversion of Love and Rayleigh wave phase velocities measured from recordings of teleseismic events at the ScanArray network. The phase velocities are measured by beamforming using three geographical subsets of the network as well as the full network. We analyze how different procedures for determining the phase velocities influence the final result and uncertainty. Joint inversion of the phase velocities in the period range 22–100 s reveals the presence of similar RA in the three subregions, with an average ξ value of about 1.05 in the subcrustal lithosphere down to at least 200 km depth. This corresponds to SH waves faster than SV by 2%–3%, a value very similar to those found in other continental regions. Considering this anisotropy together with other observables pertaining to seismic anisotropy in the area, we cannot propose a unique model satisfying all data. We can show, however, in which conditions different types of olivine crystallographic preferred orientations (CPOs) commonly observed in natural samples are compatible with the observations. CPO types associated with the preferred orientation of the a-axis, in particular the common A-type CPO, require a-axes dipping not more than 25° from the horizontal plane to explain our observations. AG-type CPO, characterized by preferred orientation of the b-axis and occurring in particular in compressional settings, can be considered as an interesting alternative interpretation of continental lithospheric anisotropy, provided the olivine b-axis is dipping by at least 60°.